Research of Operation Factors of the of Bullerjan Stove in the Program Environmentfor 3D Simulation - Kagramanyan, A.; Onishchenko, A.; Babichenko, J.; Podoprigora, A. (International Journal of Engineering and Technology, 2018)
The article is devoted to the calculation of the thermal power of the Bullerjan stove according to a preconstructed model, which is realized in the 3D modeling environment of SolidWorks 2016. The thermophysical characteristics of the processes passing through the heat pipes of the Bullerjan stove were studied in detail. In the course of the work, the values of airflow velocity and temperature distribution, the temperature distribution of a solid, the surface of the heat pipe, that in the end allowed us to obtain the values of the heat output of the oven. The obtained data made it possible to determine the value of the heat output of the oven on the mode of smoldering wood and on the mode of flaming burning. The thermal power of a Bullerjan stove and in particular, its flow simulation module for modeling the flow of liquids and gases were obtained.Â